Designprijs Rotterdam 1999. (Rotterdam : Museum Boymans van Beuningen, 1999)
van Lieshout, Joep ; Jongstra, Claudy ; van Eijk, Niels ; Luske, Sander ; Boekstra, Jan ; Wanders, Marcel ; Prins, Katja ; Jongerius, Hella ; van Grunsven, Jan ; Mark, Arno Van der ; Hans, Ineke ; Noten, Ted ; Spoor, Wouter ; Oosterhuis, Kas ; Lénard, Ilona
Designprijs Rotterdam 1999, Museum Boijmans van Beuningen, Rotterdam, 13 februari t/m 5 april 1999
boek